Recent Progress on Cellulose-Based Ionic Compounds for Biomaterials - Yang, Yang (Advanced materials (Deerfield Beach, Fla.), 2021)
© 2020 The Authors. Published by WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.